Provision of curriculum model of student life skills at primary schools of Iran - Ghabakhlou, Behzad (2021)
This research seeks to answer the question about the appropriate model of student life skills at primary schools. A comprehensive questionnaire is designed relying on the academic and industrial experts, the research background and theoretical principles in order to test the hypotheses. The reliability of questionnaire is approved through Cronbach's alpha coefficient (0.70). The research results cover the prioritization and importance of indices associated with student life skills, antecedents and consequences, and their tasks. The need for education and establishment of this skill improves the relations in learning. This is can facilitate the teaching-learning process due to the today's widespread and growing changes in the content of textbooks, structure, etc. On the one hand, it can largely overcome the educational challenges between parents, teachers and school. On the other hand, it can reduce learning costs. These costs include the training time in the classroom, tutor, regulated teaching methods, reduced purchase of poor-quality educational books, etc. These skills can also protect students from imposed teaching damages such as meaningful learning through repetition and practice. Furthermore, these skills enable the school principals to have higher accuracy and quality in their tasks such as educational supervision, control and decision-making, and the intra and extra-school communications. From principals' perspective, the self awareness has the higher rank than other components. From teachers' perspective, the scientific and technological skills have higher rank than other components; and from principals' perspective, the training time has better rank. Moreover, the teachers think that the personal factors have better ranks. Among the components, the life skill has higher rank.